Simulation modelling of service contracts within the context of Product-Service Systems (PSS). - Phumbua, Sarocha (Cranfield University, 2012)
This thesis deals with the decision support tools for service contracting within the context of Product-Service Systems (PSS). The research contributes to the modelling constructs that can support modellers in developing service contract simulation models in an effective and efficient manner. Overall, the models can assist manufacturers to understand implications of contracting decisions that may either lead to profitable solutions or loss of business opportunities. PSS is recognised as a survival strategy for many manufacturers to sustain their market competitiveness. It is an emerging manufacturing paradigm that integrates services into products to ensure the required capability or availability of products. This concept is often delivered as long-term service contracts which can be made in separation or together with product acquisition. As the contracts can span over decades, the manufacturers need to absorb the future risks. For this reason, a decision support tool that allows the risks and rewards to be visualised and ultimately support contract design is in urgent need. However, PSS has various characteristics beyond the traditional product-selling businesses and involves potential dynamic behaviour. Existing tools are inadequate to effectively analyse the issues and also to be reused across cases or during the contract delivery phase. For this reason, this thesis intends to provide modelling constructs that enhance effective and efficient development of simulation models for PSS offerings To accomplish this aim, various simulation modelling techniques have been first explored from the literature and through the practical model developments to identify the backbone of the constructs. The hybrid Discrete-Event Simulation and Agent-Based Simulation has subsequently been selected as the most suitable technique to represent the PSS cases. This technique was applied in four reported cases to generalise the modelling approach. All the developed models have been verified and validated using several methods. The approach was then analysed and refined to enhance efficiency in building models. The refined approach was used to form the modelling constructs. The constructs were validated using three other cases and tested by three other modellers with different simulation background. The results have demonstrated the applicability, practicality, feasibility, and efficiency of the constructs. The outcomes of this research are the final modelling constructs which provide significant contributions academically and practically. Academically, this research provides a new way of capturing PSS characteristics and dynamic behaviour, and brings together PSS theoretical research, operational planning and decision support tools. Practically, manufacturers can effectively analyse the implication of service contracts and modellers can rapidly develop service contract simulation models.